Tit for Tat: A Case Series of Hollow Viscus and Vascular Compressions - Vinithra Ragunathan; Saravanakumar Sengotaiyan; Malathi Vaidhiyanathan; Kiran Kumar (Journal of Gastrointestinal and Abdominal Radiology)
Background Abdominopelvic vascular and hollow viscus compression syndromes present unique challenges in radiological diagnosis, often requiring thorough exclusion of other pathologies. Recognizing these rare syndromes is essential for accurate differential diagnosis and timely treatment, reducing morbidity and mortality. This case series aims to share notable experiences in identifying unusual compression syndromes through radiological findings.